Analysis Of Excretory-Secretory Antigen Of Entamoeba histolytica For Detection Of Amoebic Liver Abscess - Wong, Weng Kin (2011)
Amoebiasis is an enteric protozoan disease caused by Entamoeba histolytica. It affects 50 million people worldwide and causes up to 100,000 fatal cases annually. Amoebic liver abscess (ALA) is the most common clinical manifestation of extraintestinal amoebiasis. It can lead to fatal outcome if early diagnosis and treatment are not obtained. To date, diagnosis of ALA is dependent on clinical history, radiological imaging, and laboratory diagnosis. Serodiagnosis is widely used because it is non-invasive and easy to perform.